New roles and competencies of teachers in the ICT-mediated learning environment of Russian universities - I. N. Ainoutdinova (Obrazovanie i Nauka, 2022)
Introduction. The research considers organisational and functional changes in the learning environment of Russian universities mediated by the spread of ICTs in education. ICTs affect the structure and content of curriculum and the relationship of participants in the educational process, which actualises the need to revise a place, roles, knowledge and competencies of humanities teachers. External and internal factors induce teachers to change approaches, methods and teaching technologies in accordance with the social request for high quality training of future professionals in the ICT-mediated realities and improve their ICT proficiency to meet the demands of the day. The best model of ICT-mediated learning environment will function on the basis of technologisation, interdisciplinarity, practice orientation, student focus and multicultural diversity.Aim. The purpose of this study was to identify, analyse and assess the determining factors that accompany, actualise and influence the process of transformation of the place, roles, skills and competencies of teachers in the ICT-mediated learning environment of universities in Russia.Methodology and research methods. The study was conducted within a framework of social, pedagogical, integrative, contextual, competency-based and comparative approaches, covering all aspects of academic activities of teachers and students in the ICT-mediated learning environment. Both qualitative and quantitative research methods were used to collect and analyse the relevant data. Analysis, synthesis and comparison were used to study and summarise scientific information; observations, questionnaires and survey were carried out within the experimental section, followed by a subsequent statistical analysis. A holistic approach allowed to create a classification of the ICT-based roles and skills of teachers and to develop the authors’ scale of gradation of ICT proficiency.Results. The conceptual apparatus is concretised; conditions for the ICTs inclusion in education are defined; the authors’ classification of the roles, skills and competencies of teachers for ICT-based professional activity, growth and development is given; the authors’ diagnostic scale (toolkit) for rating and grading humanities teachers’ level of ICT proficiency is designed and presented.Scientific novelty. The scientific novelty of the work lies in the definition and description of the systemic integrity of educational content based on knowledge and technology, the appropriate conditions for integration of ICT in the curriculum, the level of teachers’ ICT proficiency sufficient for the learning needs of their students and the expected learning outcomes.Practical significance. The authors’ classification of the roles, skills and competencies and the diagnostic scale (toolkit) for rating and grading the level of ICT-proficiency can be used in refresher courses for humanities teachers for their professional training, growth and development.